Penyediaan Tempat Sampah Dalam Meningkatkan Kesadaran Pemilahan Sampah SMAN 1 Wolo - Wahdan Alfian; Musdalifa Musdalifa; Dilla Dilla; Nurul Fadillah Slamat; Putri Mawar; Sri Asriani; Dian Permana (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The increase in activities within the school environment has led to a rise in the amount of waste generated each day. However, students’ awareness of waste segregation remains relatively low, which negatively affects the cleanliness and comfort of the school environment. The School Field Practice Program (PLP) at SMAN 1 Wolo implemented an initiative to provide separate waste bins for organic and inorganic waste as an effort to enhance students’ awareness and responsibility in waste management. The method used in this program involved direct observation to identify sanitation needs at several strategic locations within the school. Subsequently, waste bins were prepared and placed according to waste type. The results of the program indicate an improvement in students’ environmental awareness and a reduction in littering behavior. This program contributed to creating a cleaner, more orderly, and more comfortable school environment for all members of SMAN 1 Wolo.